Smart Door Lock System: A Mobile Application Development Based on IoT Technology - Muhammad A. Hanifullah; Kurniawan D. Irianto (International Journal Software Engineering and Computer Science (IJSECS), 2025)
The research introduces a miniature IoT-based smart door lock system paired with a custom Android application called Jenaela. The system tackles security vulnerabilities inherent in conventional pin tumbler locks, which remain susceptible to lock-picking techniques and provide restricted access control capabilities. The hardware architecture incorporates an ESP32 DOIT V1 microcontroller, PN532 NFC module, relay with optocoupler integration, DC-to-DC step-up converter, and 12V solenoid lock. The software solution features Jenaela, developed using TypeScript and React Native framework, deployed through Expo toolkit and EAS Build Preview. Rather than relying on third-party platforms like Blynk, Jenaela delivers complete customization and superior control mechanisms. Core functionalities encompass user authentication, RFID tag registration and deletion, LAN-based device discovery, and unlocking through both RFID and remote switch methods. Functional testing via Black Box methodology verified proper operation of all features. RFID unlocking demonstrated faster response times compared to WAN-based unlocking due to reduced system dependencies. Results validate the practicality and effectiveness of integrating IoT hardware with custom mobile applications to enhance security through dual access methods and real-time database interaction.